Values in the Strategic Management of a Modern Russian University - N. D. Tskhadaya (Высшее образование в России)
The paper reveals the logic of motivating function of values in relation to scientific and pedagogical staff of a University, substantiates the positive mutual influence of learning and educational processes. According to the four tier model of university organizational culture there are two channels for transmission and reproduction of university values – communicational and symbolic.The value scope of Ukhta State Technical University includes eight value guidelines, which determine the main areas of educational work. As a tool for organization and monitoring the effectivenessof the educational process at the University a model of “value-competence parallelepiped” was introduced. This model is a result of analytical amalgamation of two matrixes – matrix of generalcompetences and disciplines providing their formation and development and matrix of educational work at the University. Three dimensions of the model are formed by 1) a list of the main generalcultural competences, 2) a list of value guidelines for educational work, 3) the unified list of basic disciplines and principal forms of educational work the University carries out. The model of “valuecompetence parallelepiped” aims at attainment of the organic unity of learning programs, educational and extra-curricular work.The University has carried out a number of cultural and social projects, which influenced greatly on the regional environment and community. This became the foundation for the realization of it’s“third mission”. The University’s interaction model with community includes five areas such as con solidation of society, enlightenment, support, mobilization of society and branding. This work fosters University’s transformation into a centre of social development of Komi Republic. Participation of Ukhta State Technical University in global value competition and the potential of University’s socio-cultural projects boost the development of local and regional communities